Hydrological shifts from vegetation restoration in semi-arid regions: insights from the typical watersheds of the Yellow River - Hao Jia; Biqing Tian; Xiaoyan Song; Wenyi Sun; Xingmin Mu (Ecological Indicators, 2025)
Vegetation restoration in semi-arid regions presents complex tradeoffs between ecological benefits and hydrological impacts. This study focused on three representative watersheds Loess Plateau the middle of the Yellow River in China—Huangfu (HFC), Yanhe (YH), and Juhe (JH)—each undergoing distinct land use scenarios: grassland restoration, conversion of cropland to artificial forest, and predominance of forest cover, respectively. We utilized the Soil and Water Assessment Tools (SWAT) to evaluate the impact of “Grain for Green” initiative on various hydrological elements—streamflow, evapotranspiration, soil moisture, and water yield. In these watersheds, vegetation restoration has resulted in a 10.86–43.47 mm increase in evapotranspiration, a 1.38–24.89 mm decrease in soil moisture, a 5.13 mm to 26.89 mm reduction in annual runoff depth, and a 5.94–18.58 mm decrease in water yield. Specifically, Natural grassland restoration in the HFC watershed increased evaporation by 15.06 mm, reduced soil moisture by 1.38 mm, reduced annual average runoff depth by 5.13 mm, and decreased water yield 11 mm. Large-scale conversion of cropland to artificial forest in the YH watershed significantly resulted in an increase in evaporation by 43.47 mm, accompanied by a reduction in soil moisture by 24.89 mm, meanwhile, vegetation restoration enhanced the catchment capacity of the watershed, reducing the annual runoff depth by 26.89 mm and the water yield by 18.58 mm. Nature forests in the JH watershed maintained stable precipitation-streamflow coupling relationship despite climate variability, and with the increase of natural forest land, the streamflow in the watershed decreased by 6.86 mm. This study provides robust quantitative insights into how various vegetation restoration scenarios alter key hydrological components, thereby elucidating the balance between ecosystem recovery and water resource dynamics in semi-arid watersheds.